Design, optimization, and validation of corn-strain-specific primers for fall armyworm (Spodoptera frugiperda) detection in the Philippines - HENSLY JOY P. LABONETE; BEA KATRINA R. FULGENCIO; MILLANIE P. ABATAY; MAIMONA P. AMPANG; DONNAFE J. ANCHETA; SITTIE JAMELAH R. GUMAL; ELGIE A. JIMENEZ; RIS MENOEL R. MODINA; JANNAH E. YONGCO; SHARON ROSE M. TABUGO (Smujo International, 2025)
Abstract. Labonete HJP, Fulgencio BKR, Abatay MP, Ampang MP, Ancheta DJ, Gumal SJR, Jimenez EA, Modina RMR, Yongco JE, Tabugo SRM. 2025. Design, optimization, and validation of corn-strain-specific primers for fall armyworm (Spodoptera frugiperda) detection in the Philippines. Asian J Agric 9: 844-853. The fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) is an invasive pest that threatens corn production in the Philippines. The presence of morphologically identical corn- and rice-strains, each with distinct host preferences, complicates accurate identification. Molecular diagnostics are significant in understudied regions of the country, such as Mindanao where S. frugiperda invasions are rapidly expanding, with primers offering reliable support in pest surveillance. This study developed and optimized corn-strain-specific primers (FAWC1–FAWC5) using ancestral Cytochrome Oxidase I (COI) haplotypes (GenBank U72974, U72976) and Primer3 in Geneious Prime (v2023.2.1). In silico PCR and specificity assessments confirmed optimal primer characteristics (20-22 bp, 57.5-60.3 °C Tm, 50-55% GC), amplicon sizes of 100-250 bp, and absence of secondary structures. The standardized annealing temperature for amplification is 53.7°C to ensure efficient primer binding and workflow consistency. The applied step-wise experimental validation ensured that all primer sets adhered rigorous technical standards supported by wet-lab testing which narrowed the best-performing candidates to FAWC3, FAWC4, and FAWC5. Verification using larval samples collected from corn and rice fields in Davao Oriental and corn fields in Iligan City demonstrated reliable amplification. It confirmed the dominance of the corn-strain across the tested sites, strengthening geographic validation and consistency in primer performance fit for community-level monitoring FAWC4 exhibited broad corn-strain detection capability making it suitable for initial screening, while FAWC5 provided strong lineage-specific resolution within Philippine populations. Together, these primers form a dual-function molecular toolkit that enables accurate strain-level identification, strengthens regional monitoring programs, and supports evidence-based fall armyworm management strategies in Philippine corn-growing regions.